The third form electric organ discharge of electric eels - Jun Xu (Nature Portfolio, 2021)
Abstract The electric eel is a unique species that has evolved three electric organs. Since the 1950s, electric eels have generally been assumed to use these three organs to generate two forms of electric organ discharge (EOD): high-voltage EOD for predation and defense and low-voltage EOD for electrolocation and communication. However, why electric eels evolved three electric organs to generate two forms of EOD and how these three organs work together to generate these two forms of EOD have not been clear until now. Here, we present the third form of independent EOD of electric eels: middle-voltage EOD. We suggest that every form of EOD is generated by one electric organ independently and reveal the typical discharge order of the three electric organs. We also discuss hybrid EODs, which are combinations of these three independent EODs. This new finding indicates that the electric eel discharge behavior and physiology and the evolutionary purpose of the three electric organs are more complex than previously assumed. The purpose of the middle-voltage EOD still requires clarification.